(untitled) (Vietnam Journal of Community Medicine, 2023)
Phenylketonuria (PKU) is an autosomal recessive disorder caused by the PAH gene located on chromosome 12. The disease is characterized by a defect in the enzyme phenylalanine hydroxylase (PAH), causing elevated levels of phenylalanine (Phe) in the blood and subsequently leading to neurotoxicity and mental disability. The world prevalence of PKU was about 1 in 10,000 - 20,000 newborns, still, data about PKU carriers and the disease-associated variant spectra in Vietnamese people is minimal. The advent of Next Generation Sequencing (NGS) allows the simultaneous detection of multiple genetic variants, including novel variants in numerous patients within a single test, substantially reducing the testing cost. Objectives: Our study aimed to screen the carrier frequency of the PAH gene and uncover variant spectra of this disease in Vietnamese women. Methods: 2937 women who came for a prenatal routine healthcare check at the Center of Clinical Genetics and Genomics - Ha Noi Medical University Hospital and Gene Solutions were screened for disease-associated variants of the PAH gene employing NGS. Results: Of 2937 participants, 70 women were carriers (2.4%), and 12 different disease-associated variants were detected: R408Q (1/2937), V388M (2/2937), P314T (2/2937), E280K (1/2937), R241fs (1/2937), R241C (1/2937), Y206* (1/2937), Y204C (1/2937), Q172H (56/2937), H170Q (2/2937), R111* (1/2937), L41F (1/2937). Q172H was predominant in our study. There are two rare variants that allele frequency has not been reported in ClinVar and Ensemble: L41F và R241fs. Conclusion: The data from our research will inform policymakers in constructing cost-effective genetic metabolic carrier screening programs.